2010
DOI: 10.1111/j.1478-3231.2010.02291.x
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic disorders associated with chronic hepatitis C: impact of genotype and ethnicity

Abstract: In CHC, insulin resistance is independently associated with the presence of genotypes 1/4. Ethnicity is not independently associated with metabolic disorders in patients with CHC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 35 publications
1
9
0
1
Order By: Relevance
“…Sersté et al (2010) found similar results (12.4%) in a large cohort of patients with chronic hepatitis C (18). The NCEP/ATPIII criteria would not have diagnosed almost 9.5% of the individuals with MS who were diagnosed using the IDF definition (12.1% vs. 21.6%; p <0.006).…”
Section: Discussionmentioning
confidence: 61%
“…Sersté et al (2010) found similar results (12.4%) in a large cohort of patients with chronic hepatitis C (18). The NCEP/ATPIII criteria would not have diagnosed almost 9.5% of the individuals with MS who were diagnosed using the IDF definition (12.1% vs. 21.6%; p <0.006).…”
Section: Discussionmentioning
confidence: 61%
“…In the published literature, the presence of MeS in patients with HCV varied, 12.4% in Europe and 35% in the United States (14,15). These differences are explained by the Many authors consider that, despite the fact that insulin resistance is the common etiological link, the prevalence of MeS in HCV infection is similar to that of the general population (16).…”
Section: Discussionmentioning
confidence: 99%
“…As a result, we could not further analyze how viral genotype or viral load might influence the change in insulin resistance. From the existing literature, HCV‐related insulin resistance is most likely present across different genotypes [4], although some studies suggest it is more frequent in genotypes 1 and 4 [6,32]. Further studies are warranted to elucidate whether change in insulin resistance during antiviral treatment will differ according to viral genotype.…”
Section: Discussionmentioning
confidence: 99%